Morphological and biochemical characterization of Ethiopian mustard (Brassica carinata A. Braun) germplasm grown in Central Ethiopia - Ermias Estifanos; Tileye Feyissa; Kassahun Tesfaye; Alemu Lencho; Christina Eynck (Genetic Resources)
Ethiopian mustard (Brassica carinata A. Braun) shows potential for diverse applications, including as leafy greens, green manure and oilseed feedstock for biofuels. This study evaluated the seed and oil production potential and phenotypic diversity of 49 B. carinata accessions through trials conducted in 2018 at the Holeta and Asela Research Centers in Ethiopia, using a lattice design. Data were collected on phenological, morphological, agronomic and seed quality traits. The analysis revealed significant variability across most traits, except for silique width and oil and protein content at Asela, and main raceme length and total glucosinolate content at Holeta. Combined analysis showed significant genotype-by-location interactions for flowering date, seeds per silique and seed yield per hectare, indicating a strong environmental influence on these traits. Phenotypic and genotypic correlation analyses identified strong positive correlations between leaf traits and phenology, seed yield and seed quality, while oil content was negatively associated with protein and glucosinolate content. Principal component analysis identified five components at Asela and six components at Holeta with eigenvalues greater than one, explaining over 77% of the total variation at both locations. Key traits such as plant height, seed yield and oil content contributed significantly to these principal components. Cluster analysis grouped the accessions into three clusters based on distinct trait combinations. Accessions 17545, 21373, 24203 and 24495 consistently performed well across multiple traits across sites, making them strong candidates for breeding programmes focused on improving seed yield and quality in B. carinata.